2016
DOI: 10.1002/elps.201600210
|View full text |Cite
|
Sign up to set email alerts
|

Global proteomic analysis of lysine acetylation in zebrafish (Danio rerio) embryos

Abstract: Lysine acetylation is an important post-translational modification (PTM). Since the development of MS-based proteomics technology, important roles of lysine acetylation beyond histones have focused on chromatin remodeling during the cell cycle and regulation of nuclear transport, metabolism, and translation. Zebrafish (Danio rerio) is a widely used vertebrate model in genetics and biologic studies. Although studies in several mammalian species have been performed, the mechanism of lysine acetylation in D. reri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 44 publications
2
19
0
Order By: Relevance
“…S1c ). To compare crotonylation and acetylation in zebrafish, we used a previously acquired Kac dataset in zebrafish 26 (Fig. S1d ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S1c ). To compare crotonylation and acetylation in zebrafish, we used a previously acquired Kac dataset in zebrafish 26 (Fig. S1d ).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study showed that 69% of zebrafish phosphoproteins were conserved in humans 9 . In addition, 51.7% of zebrafish Kac sites overlapped with humans and 34.5% of Kac sites were identified as human Kac sites 26 . Particularly, our dataset revealed that crotonylation of ribosomal proteins and myofilament proteins was highly enriched and evolutionarily conserved.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been reported that the metabolic process is a major biological process involving acetylation in many species, such as Danio rerio , mouse, and E . coli , indicating that Kac synthetically regulates metabolism during BmNPV infection.…”
Section: Resultsmentioning
confidence: 99%
“…The acetylomes of many species, including Bombyx mori, Streptomyces roseosporus , Synechocystis sp , Danio rerio , Escherichia coli , mouse, Drosophila melanogaster , Saccharomyces cerevisiae , Oryza sativa , Arabidopsis thaliana , and Toxoplasma gondii , have been identified . In the current study, we comprehensively examined the proteome for changes of acetylated proteins in BmNPV infected BmN cells.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to these studies focused on human disease induced by viruses or bacteria, little is known about protein acetylation in aquatic species. Recently, the lysine acetylome has been investigated in zebrafish embryos [ 26 ], Daphnia [ 27 ], and also in the pathogenic bacterium Spiroplasma eriocheiris [ 28 ]. To date, there is no report on the cellular responses of the lysine acetylome in response to viral infection in aquatic species.…”
Section: Introductionmentioning
confidence: 99%